From Vulnerability to Empowerment: Rights and Rehabilitation of Destitute and Neglected Children in Pakistan - Hina Tahir (`, 2025)
This article critically examines the precarious situation of destitute and neglected children in Pakistan, analyzing the stark disjuncture between the country's progressive legal frameworks and the grim realities of implementation. Despite a rights-based architecture, including constitutional provisions and laws like the Juvenile Justice System Act (2018), an estimated 1.5 million children remain on the streets, vulnerable to exploitation, child marriage, and institutional neglect. Through a qualitative mixed-methods approach combining document analysis, key informant interviews, and focus group discussions this study identifies a profound implementation gap fueled by insufficient organizational will, a custodial model of institutional care, and pervasive social stigma. The findings indicate that while state-run shelters are at an early stage of development. Especially outside Punjab, they are increasingly striving to provide not only safety but a more supportive environment for children. Punjab’s more established models demonstrate growing attention to psychosocial needs and efforts to strengthen children’s agency, reflecting a positive shift in state practice. In other provinces, newly established shelters are beginning to adopt similar approaches as these systems expand. Likewise, NGO-led initiatives, which traditionally combine psychosocial support with skill-building, are also working in alignment with these goals. Viewed through the combined perspectives of the Human Rights-Based Approach and Empowerment, both state and NGO models show promising movement toward more holistic and child-centered care. This article argues for a fundamental paradigm shift from a welfare-oriented to an empowerment-focused model. It concludes that sustainable rehabilitation requires an integrated pipeline that seamlessly combines legal protection, trauma-informed care, and market-relevant education to transform these children from passive recipients of charity into active, rights-bearing citizens. Keywords: Destitute Children, Child Rights, Empowerment, Rehabilitation, Pakistan, Child Protection, Human Rights-Based Approach, Social Reintegration